Clinicopathological Characteristics, Treatment and Prognosis in Duodenal Adenocarcinoma with Liver Metastasis: A SEER-Based Study - Zhu Z; Liu H; Zhong F (Clinical and Experimental Gastroenterology, 2024)
Zhengchun Zhu,1 Hong Liu,2 Fei Zhong1 1Department of Oncology, Fuyang Hospital of Anhui Medical University, Fuhe Modern Industrial Park, Fuyang, People’s Republic of China; 2Department of Cardiovascular Medicine, Fuyang Hospital of Anhui Medical University, Fuhe Modern Industrial Park, Fuyang, People’s Republic of ChinaCorrespondence: Fei Zhong, Email zhongfei@ahmu.edu.cnBackground and Objectives: Duodenal adenocarcinoma (DAC) is a rare tumor that is often accompanied by liver metastasis in advanced stages. The aim of this study was to evaluate the correlation between clinicopathological characteristics and survival in DAC patients with liver metastasis, and to explore appropriate treatment options.Methods: 482 DAC patients with liver metastasis were retrospectively identified from the Surveillance, Epidemiology and End Results (SEER) database (2011– 2020). Univariate and multivariate Cox regression analyses were performed to explore the clinicopathological factors related to survival. The Kaplan-Meier method was used to identify the independent risk factors associated with survival.Results: The 1-year overall survival (OS) and cancer-specific survival (CSS) rates for the entire cohort were 25.4% and 28.3%, and the 5-year OS and CSS rates were 2.4% and 2.9% respectively. Univariable analysis and multivariate analysis identified chemotherapy and surgery as the independent risk factors for OS and CSS. Patients who underwent chemotherapy and surgery had better CSS and OS rates, whereas radiotherapy failed to improve outcomes.Conclusion: We identified several prognostic factors of DAC with liver metastasis. Chemotherapy and surgery can prolong the survival of DAC patients with liver metastasis, which lays the foundation for identifying the optimal treatment strategy.Keywords: duodenal adenocarcinoma, liver metastasis, clinicopathological characteristics, survival, SEER database